ANALISIS IMPLEMENTASI STRATEGI PEMBELAJARAN DAN PEMANFAATAN MEDIA AJAR DALAM PEMBELAJARAN IPS PADA JENJANG SEKOLAH DASAR - Oktamefa, Selma; Chairunnisa; Mayang Sari, Putri; Zakiah, Linda; Yunus, Mahmud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyse activity and strategy in Social Study education with Kebutuhanku material in SDN Rawamangun 02. this research background comes from the importance of Social Study in developing social skill and moral for student in elementary school. Metode that been used for this research is descriptive qualitative with observation technique and interview to teacher and student in the fourth grade. Research results show that learning activity gose boring with just an lecture, discussion and questioning. Beside that, media and teaching materials in the school are still unvarity, that makes student feels bored in a long term learning. Main factor of learning inhibitor are low class management and low media inovation. Overall, Social Stusy in this school has already gone great however they are still needed to add more developt strategy that varity and contextual